Characteristics of autonomic dysfunction in neuronal intranuclear inclusion disease - Lu Zhou; Yun Tian; Yun Tian; Yun Tian; Sizhe Zhang; Bin Jiao; Bin Jiao; Bin Jiao; Xinxin Liao; Yafang Zhou; Qiao Xiao; Jin Xue; et al. (Frontiers in Neurology, 2023)
BackgroundThis study aimed to investigate the features of autonomic dysfunction (AutD) in a large cohort of patients with neuronal intranuclear inclusion disease (NIID).MethodsA total of 122 patients with NIID and 122 controls were enrolled. All participants completed the Scales for Outcomes in Parkinson’s Disease-Autonomic Questionnaire (SCOPA-AUT) and genetic screening for GGC expanded repeats within the NOTCH2NLC gene. All patients underwent neuropsychological and clinical assessments. SCOPA-AUT was performed to compare AutD between patients and controls. The associations between AutD and disease-related characteristics of NIID were studied.Results94.26% of patients had AutD. Compared with controls, patients had more severe AutD in total SCOPA-AUT, gastrointestinal, urinary, cardiovascular, thermoregulatory, pupillomotor and sexual domains (all p < 0.05). The area under the curve (AUC) value for the total SCOPA-AUT (AUC = 0.846, sensitivity = 69.7%, specificity = 85.2%, cutoff value = 4.5) was high in differentiating AtuD of patients with NIID from controls. The total SCOPA-AUT was significantly and positively associated with age (r = 0.185, p = 0.041), disease duration (r = 0.207, p = 0.022), Neuropsychiatric Inventory (NPI) (r = 0.446, p < 0.01), and Activities of Daily Living (ADL) (r = 0.390, p < 0.01). Patients with onset-of-AutD had higher SCOPA-AUT scores than patients without onset-of-AutD (p < 0.001), especially in the urinary system (p < 0.001) and male sexual dysfunction (p < 0.05).ConclusionSCOPA-AUT can be used as a diagnostic and quantitative tool for autonomic dysfunction in NIID. The high prevalence of AutD in patients suggests that NIID diagnosis should be considered in patients with AutD, especially in those with unexplained AutD alone. AutD in patients is related to age, disease duration, impairment of daily living ability, and psychiatric symptoms.